The Influence of Green Trust and Green Brand Image on Islamic Bank Customer Loyalty The Moderating Role of Eco-Labeling Awareness - Aulya Risky Afradini; Yenik Lidiawati; Sumin; Luqman; Nur Atiqah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The banking sector is undergoing a transformation toward sustainable business models to mitigate climate change risks, yet the emergence of "greenwashing" has increased customer skepticism. This study aims to analyze the influence of Green Trust and Green Brand Image on Islamic Bank Customer Loyalty, with Eco-Labeling Awareness as a mediating variable. Using a quantitative approach and PLS-SEM analysis on a sample of Millennial and Gen Z banking customers in Indonesia, the results reveal that Green Trust (X1) has a positive and significant effect on Customer Loyalty (Y) (T = 9.727, P = 0.000). Conversely, Green Brand Image (X2) does not significantly impact loyalty (T = 1.599, P = 0.110). Furthermore, Eco-Labeling Awareness (Z) serves as a significant mediator for the influence of Green Trust on loyalty (T = 9.727, P = 0.000), but fails to mediate the relationship between Green Brand Image and loyalty (T = 1.599, P = 0.110). These findings suggest that for Islamic banks, building deep trust through transparent environmental standards is more effective for fostering long-term loyalty than relying solely on brand image